The effect of CRX-527 on pro-inflammatory cytokine production against mycobacterium bovis BCG clone expressing the c-terminus of merozoite surface protein-1 of plasmodium falciparum - Yusoff, Wan Raihan Wan (2021)
Malaria infection is a leading cause of mortality and morbidity in African and Southeast Asian countries. TLR-4 has been shown to be important in malaria immunity and can be possibly use as an adjuvant to enhance the long-lasting immune response against BCG-MSP1C. This research was conducted to determine the effects of toll-like receptor 4 (TLR-4) agonist, CRX527, on cellular and humoral immune response against Mycobacterium bovis bacille Calmette-Guérin (BCG) expressing the C-terminus of merozoite surface protein-1 of Plasmodium falciparum (BCG-MSP1C). In this study six groups of mice (n=6 per group) were injected with 200 μl intraperitoneal phosphate buffered saline T80 (PBS-T80), 200 μl of PBS-T80 containing 2 x 106 cfu/ml of BCG or rBCG in the presence or absence of CRX527. Blood was collected from the tail veins of the mice before the start of the immunisation and 4 weeks after each immunisation. Enzyme linked immunosorbent assay (ELISA) was carried out to measure the production of TNF-α and IL-12 in the sera of the immunized mice. The findings showed that the sera of rBCG without CRX immunised group yielding the most increase in IL-12 followed by the mice injected with rBCG with CRX. In contrast, the entire mice immunised groups showed decrease production for TNF-α after the immunisation. Therefore, this combination of rBCG with TLR4 agonist can be used to create a vaccine that capable of inducing a strong and long-lasting immunity to allow the immune system to be prepared for the emergence of multidrug-resistant strains of malaria diseases.